Macrophage-Like Cells from Primary Cell Culture of Atlantic Salmon Are Capable to Phagocyte Piscirickettsia Salmonis: Apoptosis of Phagocytes Also Occurs During Infection - Imarai-Bahamonde, C; Cortez-San Martin, M (Academic Press, 2019)
Sin Resumen Disponible